Implementation of target costing in Indonesia: the influence of dynamic capabilities, dysfunctional behaviour, and success factors in manufacturing companies / Grahita Chandrarin ... [et al.] - Chandrarin, Grahita; Omar, Normah; Yuniawan, Dani; Lisetyati, Eni (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2019)
The purpose of this research is to explore and describe the implementation of the Target Costing (TC) system as well as its effect on the dynamic capabilities (DC), success factors (SF) and dysfunctional behaviours (DB) of manufacturing firms in Indonesia. As there had been no prior research conducted on the consequences of the target costing implementation in Indonesia, this study, which had been one of the projects undertaken for improving the validity of variables and costing studies in Asia Pacific countries, was therefore performed by way of surveys along with the descriptive-quantitative and multiple regression analyses for gauging its impact on the company’s internal and competitive environment. It was found that better company performance results (PR) had not only stemmed from a low DB level, but were also influenced by the resulting strong DC from the implemented TC system. Apart from demonstrating the target pricing systems as being a triggering factor of DB, this study also discovered SF as being an insignificant aspect for determining the successful implementation of the target costing system.